Efficiency and Environmental Awareness of Paddy Farmers: Stochastic Frontier Analysis vs Data Envelopment Analysis - Nerda Zura Zaibidi; Md. Azizul Baten; Razamin Ramli; Maznah Mat Kasim (International Journal of Supply Chain Management, 2018)
This study compares the paddy production efficiency and farmers environmental awareness using both stochastic frontier analysis (SFA) and data envelopment analysis (DEA), the primary data collected from paddy farmer organizations known as Pertubuhan Peladang Kawasan (PPK) under Muda Agricultural Development Authority, Kedah, Malaysia. From the results, the coefficients of area and wage are observed significant and positive impact on paddy production while the effect of overall cost, cost on seed and fertilizer are found negative but the cost on fertilizer is recorded significant. The knowledge on environment and contract with agricultural officers are two exogenous factors that has positive significant impact while the education of the farmer factor has a negative significant impact. All the PPKs performance considered is observed on an average but they have the opportunity to increase more than 50% of their production by using same amount of inputs. The performance of Kerpan PPK is found higher than that of other PPKs when the effects of exogenous factors are considered in SFA. The performance of Kubang Pasu PPK is found minimum comparing to the other PPKs using DEA which is observed similar with SFA with exogenous factors. Again, the Kepala Batas PPK is recorded higher relative performance.